Active and reactive power sharing in micro grid using droop control - Omar Feddaoui; Riad Toufouti; Labed Djamel; Salima Meziane (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The development of renewable energy contributes to the global objectives of reducing our greenhouse gas emissions, obtaining and increasing our energy efficiency. In the face of these changes, the electric-network must adapt, while maintaining a high level of reliability and a quality of energy production. To meet this objective, it is recommended to use highly developed electrical network by integrating renewable energy sources in order to adapt the energy consumption to their production, using electro-technical software information and telecommunications technologies. We are talking about intelligent grids (Smart Grid). The main objective of the work presented in this paper is the contribution to the study of intelligent network for efficient management of energy produced by several sources linked to the AC bus via the voltage inverters. Numerical simulations have been presented to validate the performance of the proposed active and reactive power controller (Droop Control).